Sobre os professores de História que atuam na rede municipal de ensino de Belo Horizonte: perfil e concepções de ensino (Práxis Educativa, 2009)
This paper presents the features of the teachers of History of the education municipal system of Belo Horizonte City (Minas Gerais State) and explores some of their conceptions of History. It shows that the group of teachers is well informed, interested in receiving support and having opportunities and resources for the development of a more creative and meaningful pedagogical practice. Keywords: Conceptions of History. Teachers of History. Educational system of Belo Horizonte City.